The Effectiveness of Cucumber Suri Juice (Cucumis Sativus) On Blood Pressure In Menopausal Hypertension - Reni Hariyanti; Suharyo Hadisaputro; Sri Sumarni; Erna Widyastuti (Universitas STRADA Indonesia, 2020)
This study was conducted to examine the effectiveness of cucumber suri juice (Cucumis Sativus) on blood pressure in hypertensive menopausal women. The study was a quasi-experimental pretest-posttest with control group design. It was 20 respondents selected by purposive sampling, divided into two groups there were intervention group (10 respondent) and control group (10 respondent). Data were analyzed used paired T test. The results showed that the decrease systolic blood pressure in the intervention group was 31,30 mmHg and diastolic blood pressure 16,60 mmHg (p value 0,000) and in the control group decreased systolic blood pressure by 2,0 mmHg and diastolic blood pressure 1.3 mmHg (p value> 0.05). There was a significant effect of cucumber suri juice on blood pressure in the intervention group. Therefore that the cucumber suri juice can be an alternative treatment among menopausal women with hypertension